High-strength and high-conductivity Cu-Cr-P alloy and preparation method thereof

By adding Cr and P elements to the copper matrix, and using melt casting method and multi-stage cold rolling deformation and aging treatment process, a high-strength, high-conductive Cu-Cr-P alloy was prepared, which solved the problems of complex process, high cost and limited conductivity in the prior art, and achieved high performance and low-cost production.

CN119753415AActive Publication Date: 2025-04-04CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411735517.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing high-strength high-conducting copper alloys are complex in the process and costly, making it difficult to prepare large-sized products, and have limited conductivity, which cannot meet the high-performance requirements in the fields of high-speed rail and integrated circuits.

Method used

Cu-Cr-P alloy is used to form nano-scale Cr particles and Cr3P particles by adding Cr and P elements to the copper matrix, which improves the strength and conductivity of the alloy. The process is simplified and cost is reduced through melt casting method and multi-stage cold rolling deformation and aging treatment process.

Benefits of technology

Cu-Cr-P alloy with high strength and high conductivity has a limit tensile strength of no less than 410 MPa, a yield strength of no less than 370 MPa, and a conductivity of no less than 88.0% IACS. It is suitable for electronic packaging materials, with simple process and low cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753415A_ABST
    Figure CN119753415A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of alloy materials, and discloses a high-strength and high-conductivity Cu-Cr-P alloy which comprises the following components in percentage by weight: 1.5-2.0% of Cr, 0.15-0.5% of P and the balance of copper and inevitable impurities. The preparation method comprises the following steps: heating and melting pure copper and pure chromium in an atmospheric melting furnace, cooling, adding a copper-phosphorus intermediate alloy, uniformly melting, and pouring into a mold to obtain a billet; and then homogenizing treatment, hot rolling deformation treatment, solution treatment, first cold rolling deformation treatment, first aging treatment, second cold rolling deformation treatment, second aging treatment, third cold rolling deformation treatment and third aging treatment are sequentially carried out, and the high-strength and high-conductivity Cu-Cr-P alloy is obtained. The conductivity of the alloy is not lower than 88.0% IACS, the ultimate tensile strength of the alloy is not lower than 410 MPa, and the yield strength of the alloy is not lower than 370 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-strength and high-conductivity copper alloys, and in particular relates to a high-strength and high-conductivity Cu-Cr-P alloy and a preparation method thereof. Background Art

[0002] High-strength and high-conductivity copper alloys are widely used in fields such as high-speed rail contact wires and integrated circuit lead frames. The main high-strength and high-conductivity copper alloys currently used are Cu-Cr alloys (tensile strength ≥350 MPa, conductivity ≥80% IACS), Cu-Cr-Zr alloys (tensile strength ≥500 MPa, conductivity ≥75% IACS), etc. With the continuous development of chip integration technology and the continuous speed-up of high-speed railways, higher requirements are placed on the strength and conductivity of copper alloys, so there is an urgent need to develop new high-strength and high-conductivity copper alloys.

[0003] The representative Cu-Cr alloy material can meet the performance requirements of high strength. Under high temperature and room temperature conditions, the limiting solid solubility of Cr atoms in the copper matrix is ​​quite different. After solution aging treatment, nano-scale Cr particles will precipitate in the copper matrix, thereby producing a strengthening effect, so that the Cu-Cr alloy has both high strength and good electrical conductivity. However, the conductivity of traditional Cu-Cr alloys is limited, and the preparation method is mostly powder metallurgy. Its composition is accurately controlled, but the process is complicated, the die cost is high, and large-sized products cannot be prepared, making it difficult to achieve industrial mass production and wide application. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a high-strength and high-conductivity Cu-Cr-P alloy and a preparation method thereof.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A high-strength and high-conductivity Cu-Cr-P alloy includes the following components by weight percentage: 1.5-2.0% Cr, 0.15-0.5% P, and the balance is copper and inevitable impurities. Adding Cr element to the alloy can form nano-scale Cr particles during the aging process due to the low solid solubility of Cr in copper, thereby strengthening the alloy; adding P element can improve the fluidity of the alloy melt and promote the uniform distribution of components. P element will also form submicron and nano-scale Cr3P particles with Cr element, promoting the precipitation of nano-scale Cr particles.

[0006] In the present application, the addition amount of Cr and P elements is also very important. If the Cr content is high (>2%), the alloy preparation is difficult due to the high melting point of Cr and the molten metal is relatively viscous. If the Cr content is low (<1.5%), the number of nanoscale Cr particles precipitated during the aging treatment is small, and sufficient strength increment cannot be provided for the alloy. If the P content is high (>0.5%), the scattering effect of the P element on electrons increases, and the electrical conductivity of the alloy will be significantly reduced. When the P content is low (<0.15%), the fluidity of the alloy melt is poor.

[0007] The high-strength and high-conductivity Cu-Cr-P alloy mentioned above preferably has an electrical conductivity of not less than 88.0% IACS, an ultimate tensile strength of not less than 410 MPa, and a yield strength of not less than 370 MPa.

[0008] As a general inventive concept, the present invention also provides a method for preparing the high-strength and high-conductivity Cu-Cr-P alloy as described above, comprising the following steps: (1) First, pure copper and pure chromium are placed in an atmospheric smelting furnace for heating and melting, then the temperature is lowered and copper-phosphorus master alloy is added, and after being melted evenly, the mixture is poured into a mold to obtain an ingot; (2) The ingot is subjected to homogenization treatment, hot rolling treatment, solution treatment, first cold rolling treatment, first aging treatment, second cold rolling treatment, second aging treatment, third cold rolling treatment, and third aging treatment in sequence to obtain the high-strength and high-conductivity Cu-Cr-P alloy.

[0009] In the above preparation method, preferably, in step (1), the heating and melting temperature is 1800-2000°C; and the copper-phosphorus master alloy is added after the temperature drops to 700-800°C.

[0010] In the above-mentioned preparation method, preferably, in step (2), the temperature of the homogenization treatment is 950-980 ° C, the time is 1-2 h, and the billet sample is water-cooled after the homogenization treatment. The purpose of the homogenization treatment is to eliminate the component segregation caused by smelting and casting. When the temperature and time of the homogenization treatment are higher than the range controlled by the present invention, the alloy ingot is easy to melt and oxidize, and the grains are easy to grow; when the temperature and time of the homogenization treatment are lower than the range controlled by the present invention, the component segregation of the alloy is not easy to be eliminated.

[0011] In the above-mentioned preparation method, preferably, in step (2), the temperature of the hot rolling deformation treatment is 900-950 ° C, the holding time is 1-2 h, the total reduction is 80-90%, the rolling is 3-4 times, the reduction of each time is 20-30%, and the sample is water-cooled after the hot rolling deformation treatment. The function of the hot rolling deformation treatment is to achieve dynamic recrystallization of the material and refine the grains. When the temperature and time of the hot rolling deformation treatment are higher than the range required by the present invention, the alloy ingot is easy to melt, the grains are easy to grow, the performance is reduced, and the heating energy consumption is high; when the temperature and time of the hot rolling deformation treatment are lower than the range required by the present invention, the alloy is easy to crack during the hot rolling deformation process and cannot play a role in refining the grains.

[0012] In the above-mentioned preparation method, preferably, in step (2), the temperature of the solution treatment is 950-980 ° C, the holding time is 1-2 h, and the sample is water-cooled after the solution treatment. The purpose of the solution treatment is to dissolve the particles that may precipitate during the hot rolling deformation process back into the matrix. When the temperature and time of the solution treatment are higher than the range required by the present invention, the alloy grains tend to grow and the performance decreases. When the temperature and time of the solution treatment are lower than the range required by the present invention, the particles precipitated during the hot rolling deformation of the alloy cannot be fully dissolved into the matrix, affecting the mechanical properties and electrical conductivity of the alloy during the subsequent deformation heat treatment process.

[0013] In the above preparation method, preferably, in step (2), the total reduction of the first cold rolling deformation treatment is 30-50%, and the rolling is performed for 2-5 times, with the reduction of each time being 10-20%. The first cold rolling deformation treatment can improve the strength of the material on the one hand, mainly because cold working will cause an increase in defects such as dislocations inside the material, thereby leading to an increase in strength; on the other hand, it is to increase the distortion energy inside the material, promote the precipitation of particles during aging treatment, and thin the material.

[0014] The total reduction of the second cold rolling deformation treatment is 30-50%, and the rolling is performed for 2-5 times, with a reduction of 10-20% for each time. The second cold rolling deformation treatment is based on the first cold rolling deformation treatment and aging treatment, and further increases defects such as dislocations, promotes further precipitation of particles, and improves the strength, hardness and conductivity of the alloy.

[0015] The total deformation of the third cold rolling deformation treatment is 30-50%, and the rolling is performed for 2-5 times, with a reduction of 10-20% in each time. The third cold rolling deformation treatment is based on the second cold rolling deformation treatment and aging treatment, and provides driving force to enable the particles to be fully separated.

[0016] In the above-mentioned preparation method, preferably, in step (2), the temperature of the first aging treatment is 450-500 ° C, and the time is 1-4 h. The purpose of the aging treatment is to precipitate the second phase particles, improve the hardness and strength of the alloy and increase the electrical conductivity. When the temperature and time of the first aging treatment are higher than the range required by the present invention, the work hardening effect provided by the cold rolling disappears too quickly, the alloy is easy to soften, and the hardness and strength are low; when the temperature and time of the first aging treatment are lower than the range required by the present invention, the second phase particles cannot be fully precipitated, affecting the electrical conductivity of the alloy.

[0017] The temperature of the second aging treatment is 400-450 °C, and the time is 1-4 h. After the second cold rolling deformation treatment, the total reduction of the cold rolling deformation treatment increases, the driving force for particle precipitation increases, and it is easy to precipitate. When the second aging temperature cannot be too high and cannot be consistent with the temperature of the first aging treatment, otherwise the particles will precipitate quickly, the alloy will soften easily, the hardness will decrease, and the overall performance will be poor. Therefore, the temperature of the second aging treatment is lower than that of the first aging treatment.

[0018] The temperature of the third aging treatment is 350-400 ° C, and the time is 1-4 h. After the third cold rolling deformation treatment, the driving force for particle precipitation is further increased, and the residual particles in the matrix are easier to precipitate. Therefore, the temperature of the third aging treatment is lower than that of the second aging treatment, and the temperature of the three aging treatments is gradually reduced. When the temperature of the multi-stage aging treatment does not meet the gradient reduction trend required by the present invention, the alloy cannot obtain excellent comprehensive mechanical and electrical conductivity properties.

[0019] The present invention adopts a melt-casting method to prepare a high-strength and high-conductivity Cu-Cr-P alloy, directly adopts cold rolling deformation and aging treatment during the hot working process, the cold rolling treatment breaks the grains, the grain size is reduced, and a large number of dislocations are introduced by cold rolling, and the dislocations provide a large number of nucleation sites for the precipitation of solid solution elements, promoting particle precipitation; through three-stage cold rolling deformation and aging treatment, the second phase particles in the alloy are fully precipitated. Therefore, nano-scale precipitation phases and fine grains are obtained in the alloy, thereby ensuring that the alloy obtains excellent comprehensive mechanical properties and conductive properties.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The copper alloy of the present invention contains two main alloying elements, Cr and P. Under high temperature and room temperature conditions, the limiting solid solubility of Cr atoms in the copper matrix is ​​quite different. After solution aging treatment, a Cr phase will precipitate in the copper matrix. Compared with other elements, P is a low-cost alloying element with little effect on conductivity and high solubility in copper. It can inhibit the coarsening of the Cr precipitation phase through the formation of the Cr3P phase, thereby hindering dislocation movement and improving the strength and conductivity of the Cu-Cr-P alloy.

[0021] (2) The electrical conductivity of the high-strength and high-conductivity Cu-Cr-P alloy of the present invention is not less than 88.0% IACS, its ultimate tensile strength is not less than 410 MPa, and its yield strength is not less than 370 MPa. It can replace electroplated copper with high preparation cost and be used in electronic packaging materials.

[0022] (3) The present invention adopts the melt-casting method to prepare the high-conductivity Cu-Cr-P alloy, which has a simple process and low cost. It can prepare large-sized products and parts with complex shapes, has a wide range of applications, and can achieve large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM picture of the tensile fracture along the rolling surface of the plate obtained after the high-strength and high-conductivity Cu-Cr-P alloy prepared in Example 5 of the present invention is subjected to step (h).

[0024] Figure 2 This is an EBSD image of the side section of the alloy plate obtained after the high-strength and high-conductivity Cu-Cr-P alloy in Embodiment 5 of the present invention is subjected to step (j). DETAILED DESCRIPTION

[0025] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0026] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0027] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0028] Embodiment 1: The high-strength and high-conductivity Cu-Cr-P alloy of the present invention comprises the following components by weight percentage: 1.5% Cr, 0.15% P, and the balance is copper and inevitable impurities.

[0029] The method for preparing the high-strength and high-conductivity Cu-Cr-P alloy in this embodiment comprises the following steps: (1) Pure copper and pure chromium are placed in a graphite crucible of an atmospheric smelting furnace and heated to melt according to the mass percentage of Cr 1.5%, P 0.15%, and Cu 98.35%. The heating and melting temperature is 1800 °C. After the pure copper and pure chromium are melted, the melt temperature is lowered to 700 °C and then the copper-phosphorus master alloy is added. After being melted evenly, the alloy is poured into a mold to obtain an ingot.

[0030] (2) The ingot obtained after step (1) was homogenized at a temperature of 950 °C for 1 h. After the homogenization treatment, the sample was water-cooled.

[0031] (3) The ingot obtained after step (2) is subjected to hot rolling deformation treatment. The hot rolling deformation treatment temperature is 900 °C, the holding time is 2 h, the total reduction is 80%, and the rolling is performed for 4 passes. The reduction of each pass is 20%. After the hot rolling treatment, the sample is water-cooled.

[0032] (4) The hot-rolled sample obtained after step (3) was subjected to a solution treatment at a temperature of 950 °C and a holding time of 1 h. After the solution treatment, the sample was water-cooled.

[0033] (5) The solid solution sample obtained after step (4) is subjected to the first cold rolling deformation treatment, the total reduction of the cold rolling deformation treatment is 30%, and the rolling is performed for 3 times, with a reduction of 10% in each time.

[0034] (6) The cold-rolled sample obtained in step (5) is subjected to a first aging treatment at a temperature of 450 °C and a time of 1 h.

[0035] (7) The aged sample obtained after step (6) is subjected to a second cold rolling deformation treatment, wherein the total reduction of the cold rolling deformation treatment is 40%, and the rolling is performed for 4 passes, with a reduction of 10% in each pass.

[0036] (8) The cold-rolled sample obtained after step (7) is subjected to a second aging treatment at a temperature of 400 °C and a time of 1 h.

[0037] (9) The aged sample obtained after step (8) is subjected to a third cold rolling deformation treatment, wherein the total deformation amount of the cold rolling deformation treatment is 50%, the rolling is performed for 5 passes, and the reduction amount of each pass is 10%.

[0038] (10) The cold-rolled sample obtained after step (9) is subjected to a third aging treatment at a temperature of 350 °C for 1 h to obtain a high-strength and high-conductivity Cu-Cr-P alloy.

[0039] Embodiment 2: The high-strength and high-conductivity Cu-Cr-P alloy of the present invention comprises the following components by weight percentage: 1.75% Cr, 0.15% P, and the balance is copper and inevitable impurities.

[0040] The method for preparing the high-strength and high-conductivity Cu-Cr-P alloy in this embodiment comprises the following steps: (1) Pure copper and pure chromium are prepared according to the mass percentage of Cr 1.75%, P 0.15%, and Cu 98.1%. Pure copper and pure chromium are placed in a graphite crucible of an atmospheric smelting furnace for heating and melting. The heating and melting temperature is 2000 °C. After the pure copper and pure chromium are melted, the melt temperature is lowered to 800 °C and then copper-phosphorus master alloy is added. After being melted evenly, the mixture is poured into a mold to obtain an ingot.

[0041] (2) The ingot obtained after step (1) was homogenized at a temperature of 980 °C for 1 h. After the homogenization treatment, the sample was water-cooled.

[0042] (3) The ingot obtained after step (2) is subjected to hot rolling deformation treatment. The hot rolling deformation treatment temperature is 900 °C, the holding time is 3 h, the total reduction is 85%, and the rolling is performed for 4 passes. The reduction of each pass is about 21.3%. After the hot rolling deformation treatment, the sample is water-cooled.

[0043] (4) The hot-rolled sample obtained after step (3) was subjected to a solution treatment at a temperature of 950 °C and a holding time of 2 h. After the solution treatment, the sample was water-cooled.

[0044] (5) The solid solution sample obtained after step (4) is subjected to the first cold rolling deformation treatment, the total reduction of the cold rolling deformation treatment is 50%, and the rolling is performed for 5 times, with a reduction of 10% in each time.

[0045] (6) The cold-rolled sample obtained in step (5) is subjected to a first aging treatment at a temperature of 500 °C and a time of 1 h.

[0046] (7) The aged sample obtained after step (6) is subjected to a second cold rolling deformation treatment, wherein the total reduction of the cold rolling deformation treatment is 40%, and the rolling is performed for 4 passes, with a reduction of 10% in each pass.

[0047] (8) The cold-rolled sample obtained after step (7) is subjected to a second aging treatment at a temperature of 450 °C and a time of 1 h.

[0048] (9) The aged sample obtained after step (8) is subjected to a third cold rolling deformation treatment, wherein the total deformation amount of the cold rolling deformation treatment is 50%, the rolling is performed for 5 passes, and the reduction amount of each pass is 10%.

[0049] (10) The cold-rolled sample obtained after step (9) is subjected to a third aging treatment at a temperature of 400 °C for 1 h to obtain a high-strength and high-conductivity Cu-Cr-P alloy.

[0050] Embodiment 3: The high-strength and high-conductivity Cu-Cr-P alloy of the present invention comprises the following components by weight percentage: 1.5% Cr, 0.5% P, and the balance is copper and inevitable impurities.

[0051] The method for preparing the high-strength and high-conductivity Cu-Cr-P alloy in this embodiment comprises the following steps: (1) Pure copper and pure chromium are prepared according to the mass percentage of Cr 1.5%, P 0.5% and Cu 98.0%. Pure copper and pure chromium are placed in a graphite crucible of an atmospheric smelting furnace for heating and melting. The heating and melting temperature is 2000 °C. After the pure copper and pure chromium are melted, the melt temperature is lowered to 750 °C and then copper-phosphorus master alloy is added. After being melted evenly, the mixture is poured into a mold to obtain an ingot.

[0052] (2) The ingot obtained after step (1) was homogenized at a temperature of 950 °C for 2 h. After the homogenization treatment, the sample was water-cooled.

[0053] (3) The ingot obtained after step (2) was hot rolled at a temperature of 950°C, a holding time of 2 h, a total reduction of 80%, four passes, and a reduction of 20% for each pass. After the hot rolling treatment, the sample was water-cooled.

[0054] (4) The hot-rolled sample obtained after step (3) was subjected to a solution treatment at a temperature of 970 °C for a holding time of 1 h. After the solution treatment, the sample was water-cooled.

[0055] (5) The solution sample obtained after step (4) was subjected to the first cold rolling treatment, the total reduction of the cold rolling treatment was 30%, and the rolling was performed for 3 passes, with a reduction of 10% in each pass.

[0056] (6) The cold-rolled sample obtained in step (5) is subjected to a first aging treatment at a temperature of 475°C and a time of 4 h.

[0057] (7) The aged sample obtained after step (6) is subjected to a second cold rolling deformation treatment, wherein the total reduction of the cold rolling deformation treatment is 30%, the rolling is performed for 3 passes, and the reduction of each pass is 10%.

[0058] (8) The cold-rolled sample obtained after step (7) is subjected to a second aging treatment at a temperature of 425 °C and a time of 4 h.

[0059] (9) The aged sample obtained after step (8) is subjected to a third cold rolling deformation treatment, wherein the total deformation amount of the cold rolling deformation treatment is 40%, the rolling is performed in two passes, and the reduction amount of each pass is 20%.

[0060] (10) The cold-rolled sample obtained after step (9) is subjected to a third aging treatment at a temperature of 375 °C for 4 h to obtain a high-strength and high-conductivity Cu-Cr-P alloy.

[0061] Embodiment 4: The high-strength and high-conductivity Cu-Cr-P alloy of the present invention comprises the following components by weight percentage: 2.0% Cr, 0.5% P, and the balance is copper and inevitable impurities.

[0062] The method for preparing the high-strength and high-conductivity Cu-Cr-P alloy in this embodiment comprises the following steps: (1) Pure copper and pure chromium are prepared according to the mass percentage of Cr 2.0%, P 0.5%, and Cu 97.5%. Pure copper and pure chromium are placed in a graphite crucible of an atmospheric smelting furnace for heating and melting. The heating and melting temperature is 1900°C. After the pure copper and pure chromium are melted, the melt temperature is lowered to 800°C and then copper-phosphorus master alloy is added. After being melted evenly, the mixture is poured into a mold to obtain an ingot.

[0063] (2) The ingot obtained after step (1) was homogenized at a temperature of 970 °C for 2 h. After the homogenization treatment, the sample was water-cooled.

[0064] (3) The ingot obtained after step (2) was hot rolled at a temperature of 925°C, a holding time of 3 h, a total reduction of 90%, 3 passes, and a reduction of 30% for each pass. After the hot rolling treatment, the sample was water-cooled.

[0065] (4) The hot-rolled sample obtained after step (3) was subjected to a solution treatment at a temperature of 950 °C and a holding time of 2 h. After the solution treatment, the sample was water-cooled.

[0066] (5) The solid solution sample obtained after step (4) is subjected to the first cold rolling deformation treatment, the total reduction of the cold rolling deformation treatment is 50%, and the rolling is performed for 5 times, with a reduction of 10% in each time.

[0067] (6) The cold-rolled sample obtained in step (5) is subjected to a first aging treatment at a temperature of 475 °C and a time of 2 h.

[0068] (7) The aged sample obtained after step (6) is subjected to a second cold rolling deformation treatment, wherein the total reduction of the cold rolling deformation treatment is 40%, the rolling is performed in two passes, and the reduction of each pass is 20%.

[0069] (8) The cold-rolled sample obtained after step (7) is subjected to a second aging treatment at a temperature of 425 °C and a time of 2 h.

[0070] (9) The aged sample obtained after step (8) is subjected to a third cold rolling deformation treatment, wherein the total deformation amount of the cold rolling treatment is 30%, the rolling is performed for 3 passes, and the reduction amount of each pass is 10%.

[0071] (10) The cold-rolled sample obtained after step (9) is subjected to a third aging treatment at a temperature of 350 °C for 2 h to obtain a high-strength and high-conductivity Cu-Cr-P alloy.

[0072] Embodiment 5: The high-strength and high-conductivity Cu-Cr-P alloy of the present invention comprises the following components by weight percentage: 2.0% Cr, 0.25% P, and the balance is copper and inevitable impurities.

[0073] The method for preparing the high-strength and high-conductivity Cu-Cr-P alloy in this embodiment comprises the following steps: (1) Pure copper and pure chromium are prepared according to the mass percentage of Cr 2.0%, P 0.25%, and Cu 97.75%. Pure copper and pure chromium are placed in a graphite crucible of an atmospheric smelting furnace for heating and melting. The heating and melting temperature is 2000°C. After the pure copper and pure chromium are melted, the melt temperature is lowered to 700°C and then copper-phosphorus master alloy is added. After being melted evenly, the alloy is poured into a mold to obtain an ingot.

[0074] (2) The ingot obtained after step (1) was homogenized at a temperature of 980 °C for 2 h. After the homogenization treatment, the sample was water-cooled.

[0075] (3) The ingot obtained after step (2) is hot rolled. The hot rolling deformation treatment temperature is 900 °C, the holding time is 1 h, the total reduction is 90%, and the rolling is performed for 3 passes. The reduction for each pass is 30%. After the hot rolling treatment, the sample is water-cooled.

[0076] (4) The hot-rolled sample obtained after step (3) was subjected to a solution treatment at a temperature of 980 °C for a holding time of 2 h. After the solution treatment, the sample was water-cooled.

[0077] (5) The solid solution sample obtained after step (4) is subjected to the first cold rolling deformation treatment, the total reduction of the cold rolling deformation treatment is 50%, and the rolling is performed for 5 times, with a reduction of 10% in each time.

[0078] (6) The cold-rolled sample obtained in step (5) is subjected to a first aging treatment at a temperature of 500 °C and a time of 0.25 h.

[0079] (7) The aged sample obtained after step (6) is subjected to a second cold rolling deformation treatment, wherein the total reduction of the cold rolling deformation treatment is 50%, the rolling is performed for 5 passes, and the reduction of each pass is 10%.

[0080] (8) The cold-rolled sample obtained after step (7) was subjected to a second aging treatment at a temperature of 400 °C for 2 h. The SEM image of the tensile fracture of the aged sample along the rolled surface is shown in FIG. Figure 1 shown.

[0081] (9) The aged sample obtained after step (8) is subjected to a third cold rolling deformation treatment, wherein the total deformation amount of the cold rolling deformation treatment is 50%, the rolling is performed for 5 passes, and the reduction amount of each pass is 10%.

[0082] (10) The cold-rolled sample obtained after step (9) was subjected to a third aging treatment at a temperature of 350 °C for 2 h to obtain a high-strength and high-conductivity Cu-Cr-P alloy. The EBSD image of its side section is shown in FIG. Figure 2 shown.

[0083] Comparative Example 1: The Cu-Cr-P alloy of this comparative example includes the following components, measured in weight percentage: 5.0% Cr, 1.0% P, and the balance being copper and inevitable impurities.

[0084] The Cu-Cr-P alloy of this comparative example is different from that of Example 1 only in the alloy composition, and its preparation method is exactly the same as that of Example 1.

[0085] Comparative Example 2: The Cu-Cr-P alloy of this comparative example has the same alloy composition as that of Example 2, except that the hot rolling deformation treatment temperature in step (3) of the preparation method of this comparative example is 700°C, the total reduction is 50%, and the other process parameters are the same as those of Example 2.

[0086] Comparative Example 3: The Cu-Cr-P alloy of this comparative example has the same alloy composition as that of Example 3. The difference between the preparation method of the Cu-Cr-P alloy of this comparative example and that of Example 3 is that the solid solution sample obtained after step (4) is subjected to only one cold rolling treatment and one aging treatment, i.e., the Cu-Cr-P alloy is obtained, wherein the total cold rolling reduction is 70.6%, the rolling is performed for 5 passes, the reduction for each pass is 14.12%, the aging temperature is 450°C, and the time is 3 h.

[0087] Comparative Example 4: The Cu-Cr-P alloy of this comparative example has the same alloy composition as that of Example 4. The difference between the preparation method of the Cu-Cr-P alloy of this comparative example and that of Example 4 is that in step (8), the temperature of the second aging treatment is 500°C and the time is 2 h. The other process parameters are the same as those of Example 4.

[0088] Comparative Example 5: The Cu-Cr-P alloy of this comparative example has the same alloy composition as that of Example 5. The difference between the preparation method of the Cu-Cr-P alloy of this comparative example and that of Example 5 is that in step (9), the total cold rolling deformation of the third cold rolling treatment is 90%, and the rolling is performed for 3 passes with a reduction of 30% in each pass. The other process parameters are the same as those of Example 5.

[0089] The tensile and conductive properties of the high-strength and high-conductivity Cu-Cr-P alloys prepared in the above embodiments and comparative examples were tested, and the ultimate tensile strength (GB / T 228.1-2021), yield strength (GB / T 228.1-2021), conductivity (GB / T 32791-2016), etc. are shown in Table 1.

[0090] Table 1 Properties of Cu-Cr-P alloys prepared in various embodiments and comparative examples

[0091] As shown in Table 1, the test results of Comparative Example 1 and Example 1 show that too high Cr and P content will lead to a decrease in the mechanical properties and electrical conductivity of the alloy, which is due to the increase in the number of solid solution atoms remaining in the matrix. The test results of Comparative Example 2 and Example 2 show that too low hot rolling temperature and total reduction will lead to excessive grain size and performance degradation. The comparison results of Comparative Example 3 and Example 3 show that when the total cold rolling reduction is basically the same, compared with the single cold rolling aging treatment process, the multiple cold rolling aging treatment process allows the particles in the alloy to be fully precipitated, thereby strengthening the alloy and improving the conductivity. The comparison results of Comparative Example 4 and Example 4 show that too high aging temperature will lead to too fast precipitation of second phase particles, and its strengthening effect is weaker than the high temperature softening effect, and the strength and conductivity of the alloy will decrease. The comparison results of Comparative Example 5 and Example 5 show that too high cold rolling reduction will lead to too fast precipitation of particles, and the strengthening effect in the subsequent aging treatment process is significantly weaker than the softening effect, and the strength of the alloy is reduced.

[0092] In summary, the Cu-Cr-P alloy prepared by the process and parameters of the present invention has excellent comprehensive properties, an ultimate tensile strength of not less than 410 MPa, a yield strength of not less than 370 MPa, and an electrical conductivity of 88.0% IACS.

Claims

1. A high-strength and high-conductivity Cu-Cr-P alloy, characterized in that: Calculated by weight percentage, it includes the following components: Cr 1.5-2.0%, P 0.15-0.5%, and the balance is copper and inevitable impurities.

2. The high-strength and high-conductivity Cu-Cr-P alloy according to claim 1, characterized in that: The electrical conductivity of the high-strength and high-conductivity Cu-Cr-P alloy is not less than 88.0% IACS, the ultimate tensile strength is not less than 410 MPa, and the yield strength is not less than 370 MPa.

3. A method for preparing a high-strength and high-conductivity Cu-Cr-P alloy as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) First, pure copper and pure chromium are placed in an atmospheric smelting furnace for heating and melting, then cooled, copper-phosphorus master alloy is added, and after being melted evenly, it is poured into a mold to obtain an ingot; (2) The ingot is subjected to homogenization treatment, hot rolling deformation treatment, solution treatment, first cold rolling deformation treatment, first aging treatment, second cold rolling deformation treatment, second aging treatment, third cold rolling deformation treatment, and third aging treatment in sequence to obtain the high-strength and high-conductivity Cu-Cr-P alloy.

4. The preparation method according to claim 1, characterized in that In step (1), the heating and melting temperature is 1800-2000°C; after the temperature drops to 700-800°C, the copper-phosphorus master alloy is added.

5. The preparation method according to claim 1, characterized in that In step (2), the temperature of the homogenization treatment is 950-980°C and the time is 1-2 h. After the homogenization treatment, the billet sample is water-cooled.

6. The preparation method according to claim 1, characterized in that In step (2), the temperature of the hot rolling deformation treatment is 900-950 ° C, the holding time is 2-3 h, the total reduction is 80-90%, the rolling is 3-4 times, the reduction of each time is 20-30%, and the sample is water-cooled after the hot rolling deformation treatment.

7. The preparation method according to claim 1, characterized in that In step (2), the temperature of the solution treatment is 950-980°C, the holding time is 1-2 h, and the sample is water-cooled after the solution treatment.

8. The preparation method according to claim 1, characterized in that: In step (2), the total reduction of the first cold rolling deformation treatment is 30-50%, and the reduction of each pass is 10-20%; The total reduction of the second cold rolling deformation treatment is 30-50%, and the reduction of each pass is 10-20%; The total deformation amount of the third cold rolling deformation treatment is 30-50%, and the reduction amount of each pass is 10-20%. The temperature of the second aging treatment is 400-450 °C and the time is 1-4 h; The temperature of the third aging treatment is 350-400°C and the time is 1-4 h.

Citation Information

Patent Citations

  • Precipitation enhanced type brass alloy and preparation method thereof

    CN105002394A

  • Preparation process of copper alloy material for short-process lead frame

    CN113699397A

  • Process for Heat Treating Copper Base Alloys

    GB1198070A

  • Production of high-strength and high-conductivity copper alloy material for electronic equipment

    JP1995258805A

  • Cu-Cr-Mg-P-Zr alloys with high electrical conductivity and high tensile strength

    KR1020120097748A